Changes in psychiatric disorder incidence patterns during the COVID-19 pandemic in Korea: a study using the nationwide universal health insurance data - Changwoo Han; Juho Choi; Hoyeon Jang; Hwa-Young Lee; Tarik Benmarhnia; Juhwan Oh (BMC Psychiatry)
Abstract Background Few studies have evaluated the incidence of various psychiatric disorders during the coronavirus disease (COVID-19) pandemic using hospital visit data for the entire population of a nation. We used Korea’s universal compulsory health insurance data to conduct a descriptive analysis to evaluate changes in psychiatric disorder incidence during the COVID-19 pandemic. Methods Hospital visit data related to psychiatric disorders were retrieved from the National Health Insurance Database. First-ever diagnosis for specific psychiatric disorders for each Korean was identified (from January 2015 to February 2023) and monthly age-standardized incidence rates were calculated. An interrupted time-series analysis was used to estimate counterfactual disease incidence rates and observed and counterfactual rates were compared using difference-in-difference framework. Results Compared to pre-pandemic period, there was a decrease in the incidence [percentage changes in monthly rate (95% confidence intervals)] of organic mental disorders [-14.6% (-18.4, -10.9)] and psychoactive substance related disorders [-12.9% (-17.5, -8.3)] during the pandemic. However, anxiety disorders [8.8% (3.1, 14.6)], behavioral syndromes associated with physiological disturbances [8.1% (4.2, 11.9)], mental retardation [8.6% (3.0, 14.2)], psychological developmental disorders [19.6% (11.5, 27.7)], childhood- and adolescent-onset behavioral and emotional disorders [45.1% (28.4, 61.8)], and unspecified mental diseases [51.8% (39.8, 63.8)] increased. Conclusions Psychological disease incidence patterns changed substantially during the pandemic in South Korea. Various pandemic-related stressors, such as disrupted lifestyles and hospital accessibility, may have influenced these changes. The causes and public health consequences of these changes require further evaluation.